How do You Want to restore?--Assessing the Public Preferences and Social Benefits of Ecological Restoration for Natural Rubber Plantation in China - Qiao, Dan; Li, Weiqin; Zhang, Desheng; Yan, Yan; Xu, Tao (Frontiers in Environmental Science, 2022)
Revealing the public’s preference for ecological restoration projects will help increase public support and improve social benefits evaluation accuracy, which is a prerequisite for implementing ecological restoration projects. This study aimed to reveal the public’s preference for natural rubber plantation restoration projects and then quantify the social benefits of these projects to provide valuable references for related policy design. Based on choice experiments, we built a hypothetical market of ecological products and conducted a field survey to obtain the public’s preferences and willingness to pay (WTP) for natural rubber plantation restoration projects. Then, a random parameters logit model was applied to obtain public preference information, and then the social benefits brought by different restoration scenarios were calculated and compared. The results showed that: 1) residents of Hainan Province had a positive attitude toward ecological restoration for natural rubber plantations and were willing to bear a personal cost. 2) respondents had significant differences in preference for attributes of restoration projects. 3) a restoration project covering 2.1 million mu of rubber plantations, prioritizing the water source protection area, focusing the implementation on state farms, and developing the under-forest breeding economy would gain more social benefits, precisely, 337.543 million yuan/year. Ecological restoration policies should pay more attention to public needs and incorporate them into future guidelines. Policymakers should focus on restoration quality instead of the restoration area. Priority should be given to rubber plantations close to the water source protection area and small householders, and an appropriate under-forest economy should be considered. This study can provide a valuable reference for policy-making related to rubber plantation restoration.